2023
DOI: 10.1371/journal.pntd.0011147
|View full text |Cite
|
Sign up to set email alerts
|

Modelling modifiable factors associated with the probability of human rabies deaths among self-reported victims of dog bites in Abuja, Nigeria

Abstract: Canine-mediated rabies kills tens of thousands of people annually in lesser-developed communities of Asia, Africa, and the Americas, primarily through bites from infected dogs. Multiple rabies outbreaks have been associated with human deaths in Nigeria. However, the lack of quality data on human rabies hinders advocacy and resource allocation for effective prevention and control. We obtained 20 years of dog bite surveillance data across 19 major hospitals in Abuja, incorporating modifiable and environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Sociodemographic factors, such as poverty and population density, have been associated with the transmission of canine and human rabies in certain contexts ( [69]. Additionally, ecological factors and attributes of the landscape, such as land cover, have been implicated in rabies transmission by wildlife species, like skunks and raccoons [70].…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic factors, such as poverty and population density, have been associated with the transmission of canine and human rabies in certain contexts ( [69]. Additionally, ecological factors and attributes of the landscape, such as land cover, have been implicated in rabies transmission by wildlife species, like skunks and raccoons [70].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the respondents had attitudes associated with higher rabies risk, as more than half (50.4%) indicated that they could play with any dog regardless of its vaccination status. Meanwhile, most rabies cases in Nigeria have been attributed to stray, free-roaming, and unvaccinated dogs [5] . Attitudes towards reporting the cases of dog bites in animals and humans to the hospital and submitting samples from suspected rabid animals for laboratory testing pose a higher risk of rabies exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, a West African country, rabies still poses a significant public health threat. Thousands of people die of rabies annually and prevalence rates ranging from 3% to 28% have been reported among dogs in different regions of the country [5] . The domestic dog is the most common transmitter of rabies in Nigeria and many cases of rabies are due to bites by dogs, especially free-roaming dogs [6] .…”
Section: Introductionmentioning
confidence: 99%